2003
DOI: 10.1029/137gm15
|View full text |Cite
|
Sign up to set email alerts
|

The continental record of stage 11: A review

Abstract: The review of terrestrial records of marine isotope stage 11 indicates that they are mostly yielded by pollen and loess sequences. They occur in different locali ties around the world and show different time resolution and environmental con ditions. Other records are discussed which correspond to more particular condi tions, i.e., the Lake Baikal deposits, or the terrestrial malacofauna from tufa de posits in Western Europe. If almost all the records indicate moister conditions than present, the temperature es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, some marine data sets have been interpreted as showing that during MIS 11, sea surface temperatures were no warmer than recent temperatures [Hodell et al, 2000;King and Howard, 2000;Becquey and Gersonde, 2002, 2003a, 2003b]; yet until the present, the WAIS still survives. In contrast, various terrestrial temperature records have been interpreted as showing that MIS 11 was warmer than both MIS 5e and the Holocene (see review by Rousseau [1999]). Sea level records have suggested a sea level rise above Holocene levels of up to +20 m during MIS 11 [Kindler and Hearty, 2000;Hearty et al, 1999;Brigham-Grette, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…However, some marine data sets have been interpreted as showing that during MIS 11, sea surface temperatures were no warmer than recent temperatures [Hodell et al, 2000;King and Howard, 2000;Becquey and Gersonde, 2002, 2003a, 2003b]; yet until the present, the WAIS still survives. In contrast, various terrestrial temperature records have been interpreted as showing that MIS 11 was warmer than both MIS 5e and the Holocene (see review by Rousseau [1999]). Sea level records have suggested a sea level rise above Holocene levels of up to +20 m during MIS 11 [Kindler and Hearty, 2000;Hearty et al, 1999;Brigham-Grette, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance to this study is the occurrence of the age‐diagnostic molluscan group, the ‘ Lyrodiscus assemblage’ in Hoxnian Interglacial deposits. The group represents a distinctive suite of taxa representing forest environments (Rousseau et al ., 1992; Antoine and Limondin‐Lozouet, 2004; Limondin‐Lozouet and Antoine, 2006; Limondin‐Lozouet et al ., 2006, 2020; Cliquet et al ., 2009), and includes species representing warmer and more humid conditions than the present day (Rousseau, 2003; Preece et al ., 2007). The Lyrodiscus assemblage has been identified in a series of independently dated MIS 11 tufa deposits including Beeches Pit in Britain (Fig.…”
Section: Background and Study Areamentioning
confidence: 99%
“…The study of raised beaches located in tectonically stable regions and of ice cap dynamics during MIS11 revealed that the sea level was 6 to 13 m higher than today on average (de Vernal and Hillaire-Marcel, 2008; Elderfield et al, 2012; Roberts et al, 2012). Moreover, the analysis of terrestrial records corresponding to MIS11 has shown that this warm isotope stage was globally humid (Rousseau, 2003; Prokopenko et al, 2010; Melles et al, 2012). The configuration of astronomical parameters during MIS11, especially the weak precession, induced weaker insolation variability than for other warm isotope stages (Berger and Loutre, 2002).…”
Section: Introductionmentioning
confidence: 99%